Antibody Immunity Induced by H7N9 Avian Influenza Vaccines: Evaluation Criteria, Affecting Factors, and Implications for Rational Vaccine Design - Hu, Zenglei; Jiao, Xinan; Liu, Xiufan (Frontiers in Microbiology, 2017)
Severe H7N9 avian influenza virus (AIV) infections in humans have public health authorities around the world on high alert for the potential development of a human influenza pandemic. Currently, the newly-emerged highly pathogenic avian influenza A (H7N9) virus poses a dual challenge for public health and poultry industry. Numerous H7N9 vaccine candidates have been generated using various platforms. Immunization trials in animals and humans showed that H7N9 vaccines are apparently poorly immunogenic because they induced low hemagglutination inhibition and virus neutralizing antibody titers. However, H7N9 vaccines elicit comparable levels of total hemagglutinin (HA)-reactive IgG antibody as the seasonal influenza vaccines, suggesting H7N9 vaccines are as immunogenic as their seasonal counterparts. A large fraction of overall IgG antibody is non-neutralizing antibody and they target unrecognized epitopes outside of the traditional antigenic sites in HA. Further, the Treg epitope identified in H7 HA may at least partially contribute to regulation of antibody immunity. Here, we review the latest advances for the development of H7N9 vaccines and discuss the influence of serological criteria on evaluation of immunogenicity of H7N9 vaccines. Next, we discuss factors affecting antibody immunity induced by H7N9 vaccines, including the change in antigenic epitopes in HA and the presence of the Treg epitope. Last, we present our perspectives for the unique features of antibody immunity of H7N9 vaccines and propose some future directions to improve or modify antibody response induced by H7N9 vaccines. This perspective would provide critical implications for rational design of H7N9 vaccines for human and veterinary use.